2006
DOI: 10.1007/s11414-006-9036-0
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Mechanical Restraints in Acute Psychiatric Care Settings Using Rapid Response Teams

Abstract: This article describes the use of rapid response teams to reduce the use of mechanical restraints (i.e., restricting a person's movement through the use of a mechanical device such as a backboard, net, or papoose) in an acute psychiatric care setting. Rapid response teams have proven highly effective for emergent medical patients, but have not typically been used in behavioral health care settings. Utilizing a rapid cycle process improvement approach, a response team was convened following each episode of mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…In another, response teams to review restraint episodes was reported to improve supervision, communication between staff members at different levels and opportunities to discuss individual patient's treatment plans (40). These provide anecdotal evidence of teamwork skill and apparent positive attitude leading to lower restraint and seclusion, but were not examined explicitly by any study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In another, response teams to review restraint episodes was reported to improve supervision, communication between staff members at different levels and opportunities to discuss individual patient's treatment plans (40). These provide anecdotal evidence of teamwork skill and apparent positive attitude leading to lower restraint and seclusion, but were not examined explicitly by any study.…”
Section: Discussionmentioning
confidence: 99%
“…The review process was the primary aim of the intervention in another study (i.e. it focused on repeated restraint only), which found a reduction in restraint episodes from 21 per 1000 bed days to 14 over a 12 week period (40).…”
Section: Review Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment agencies have used the NIATx model to focus their efforts on implementation of business practices to reduce waiting times and increase continuation in treatment (Hoffman, Ford, Choi, Gustafson, & McCarty, 2008; McCarty et al, 2007; Wisdom, Hoffman, Rechberger, Seim, & Owens, 2009). The NIATx model has also helped improve patient care in behavioral health systems (Prescott, Madden, Dennis, Tisher, & Wingate, 2007). A recent NIATx initiative, Advancing Recovery, expanded the NIATx model to test its usefulness in the implementation of evidence-based practices (EBPs) related to pharmacological and behavioral therapies among chemical dependency providers and to create changes at state and payer levels that would encourage EBP adoption (Bornemeier, 2010).…”
Section: Introductionmentioning
confidence: 99%